2011
DOI: 10.3111/13696998.2011.583152
|View full text |Cite
|
Sign up to set email alerts
|

Stability of infliximab dosing in inflammatory bowel disease: results from a multicenter US chart review

Abstract: Weight-based dosing and, presumably, patient response enabled providers to find the effective infliximab dose for IBD patients. The maintenance dose and administration frequency remained stable during the initial year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Infliximab escalation was also required in 16/117 patients (14%) in the open-label extension of the ACT studies, and 36/80 patients (45%) in a large French cohort (4,18). Data from US community practices suggests that up to 40% of patients with UC require shortening of their infusion cycles, which is more common than occurs in patients with Crohn’s 6 disease (19). A number of explanations for secondary loss of response to infliximab have been proposed, including antibodies to infliximab (ATIs), differences in clearance, and innate anti-TNF antibodies (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infliximab escalation was also required in 16/117 patients (14%) in the open-label extension of the ACT studies, and 36/80 patients (45%) in a large French cohort (4,18). Data from US community practices suggests that up to 40% of patients with UC require shortening of their infusion cycles, which is more common than occurs in patients with Crohn’s 6 disease (19). A number of explanations for secondary loss of response to infliximab have been proposed, including antibodies to infliximab (ATIs), differences in clearance, and innate anti-TNF antibodies (8).…”
Section: Discussionmentioning
confidence: 99%
“…4,18 Data from US community practices suggests that up to 40% of patients with UC require shortening of their infusion cycles, which is more common than occurs in patients with Crohn's disease. 19 A number of explanations for secondary loss of response to IFX have been proposed, including antibodies to IFX (ATIs), differences in clearance and innate anti-TNF antibodies. 8 This increase in use of IFX has significant implications in terms of costs and cumulative exposure to IFX.…”
Section: Discussionmentioning
confidence: 99%
“…Data from randomised controlled trials (RCTs) and population‐based case series have reported that only ~40% of patients remain in remission or maintain a sustained response at 1 year . This gradual loss of response in many patients has led to empiric biologic dose escalation and a ‘dose‐creep’ phenomenon seen in practice There are many reasons for this secondary loss of response, but often the development of neutralising antibodies in the patient against the therapeutic protein plays a role …”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have reported high rates of loss of response to infliximab during maintenance treatment, which is similar to the results of studies on CD . Retrospective multicentre studies conducted in community clinics and university hospitals, have reported that up to 40% of patients with UC experienced loss of response to infliximab, which was more common than that reported in patients with CD . By analogy with the data available in CD patients, it is hypothesised that dose doubling or interval shortening are as effective in restoring the response to infliximab .…”
Section: Discussionmentioning
confidence: 57%